Psycholinguistic features of communication in English and Uzbek - Raxmanova Dilobar (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Abstract: This article explores the psycholinguistic characteristics of communication in English and Uzbek, focusing on how cognitive processes, cultural context, and linguistic structures influence speech production, comprehension, and interaction. By examining differences in sentence structure, semantic nuances, pragmatic conventions, and socio-cultural factors, the study highlights how speakers of both languages navigate meaning, intention, and communicative strategies. The findings provide insights into cross-linguistic communication, language teaching, and translation, emphasizing the importance of psycholinguistic awareness in effective bilingual and intercultural interaction.